Identification of nitrifiers and nitrification performance in drinking water biological activated carbon (BAC) filtration - MERTOĞLU, BÜLENT; BAKIRCI, KOZET (ELSEVIER SCI LTD, 2010)
In this study laboratory scale biological activated carbon (BAC) columns were operated with water taken from a surface water reservoir in Istanbul. The aim was to evaluate the efficiency of nitrification in columns packed with two different granular activated carbon grades (open superstructure/chemically activated and closed superstructure/steam activated carbon) and to examine the probable beneficial effect of pre-ozonation. The occurrence and diversity of ammonia-oxidizing bacteria were investigated using 16S rDNA and amoA gene based molecular techniques. Nearly complete removal of NH4+-N was achieved by nitrification in both carbon types. The nitrification efficiency did not change in columns fed with ozonated water. However, the type of feed (either raw or ozonated) played a more important role than the type of GAC with respect to the dominance of nitrifier species in BAC columns. In biofilters ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) were most closely related to Nitrosomonas spp. and Nitrospira spp. as determined by cloning and slot-blot analysis, respectively. The fraction of the AOB population in the biomass was high as detected by real-time PCR. The amoA/16S rDNA ratio varied from 28.7% to 2.1% along the depth of filters. In spite of similar removal efficiencies, BAC columns fed with ozonated water harbored different types of AOB than columns that were receiving raw water. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Nitrification; Biological activated carbon; Real-time PCR; Slot-blot hybridization; AMMONIA-OXIDIZING BACTERIA; SUBMERGED BIOFILM REACTOR; FILTERS; REMOVAL; IMPACT; OXIDATION; BIOFILTRATION; SLUDGE; ION